Increasing smallholders' intensity in cassava value web: effect on household food security in Southwest Nigeria - Adeyemo, T.A.; Abass, A.; Amaza, P.; Okoruwa, V.; Akinyosoye, V.; Salman, K.K. (2015)
Although cassava production and processing is on the increase in Nigeria, there is still a large gap to be filled in meeting the food and raw material need of the country in terms of cassava products and by-products. The reported increase in area cultivated with cassava has not been translated to higher resource use efficiency or productivity, thus cassava smallholders have low physical and economic returns on their activities. This has serious implications for their well-being attributes, chiefly food security. A value web system, involving multiple enterprises within interconnected value chains, has been proposed as a strategy for smallholders to increase resource use efficiency and financial benefits. This study examined the levels of intensity by which cassava smallholders utilise the cassava biomass using available resources. It also isolated the determinants of the different levels of participation in the cassava biomass value web. The study further investigated the effect of higher intensity of cassava biomass utilisation by smallholders on the food security status of their households with respect to their calorie intake and dietary diversity. The study also profiled the different risks to food security based on the level of intensity of the smallholders' participation in the cassava value web. The research used data from a survey of 150 cassava smallholders, from 7 local government areas in Ogun state Nigeria. The results revealed that food security status of households using the cost of calorie index generally increased with increasing intensity of participation in the cassava value web. Dietary diversity of households also increased with an increase in the intensity of participation in the cassava web. Smallholders who are multitasking are also less vulnerable to food insecurity. The study also found that smallholders are rational and respond to changes in market conditions for their products and are willing to take more active roles in the cassava value web. Policy thrust should thus focus on increasing market opportunities for smallholders which will serve as incentives to take more active roles in the cassava value web, with consequence for their productivity, income and hence food security.